Aksiologi Filsafat Ilmu: Tinjauan Sistematis Integrasi Nilai dalam Praktik Keilmuan Modern - Shintia Mulyawati; Zulbaidah; Efendi; M. Zalnur (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
This article examines the position of axiology within the philosophy of science as a normative foundation that guides the use of knowledge in the modern era, which is characterized by technological advancement and social complexity. Through a qualitative approach based on literature studies, this research explores how ethical, moral, and humanistic values are integrated into scientific practice to ensure that scientific development is not only objective but also socially responsible. The analysis indicates that modern scientific practice is never value-free; the selection of research topics, methods, and the application of scientific findings are consistently influenced by particular value orientations. The integration of values into science is essential to prevent the misuse of scientific knowledge, strengthen the responsibility of scientists, and promote innovations that prioritize human well-being. This article asserts that axiology must serve as a key pillar in the development and application of science so that scientific processes remain relevant, ethical, and positively contributive to modern life.